The Relationship between the Implementation of the Occupational Safety and Health Management System (SMK3) and Employee Performance - Clerys F Barani; Richard Palilingan; Prycilia Mamuaja (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The implementation of the Occupational Safety and Health Management System (SMK3) is an important effort in creating a safe and healthy work environment and increasing employee productivity. The high number of work accidents both globally and nationally shows that the implementation of SMK3 is not optimal. This condition can have an impact on a decrease in employee performance. Therefore, this study aims to determine the relationship between the implementation of SMK3 and employee performance at PT PLN (Persero) ULP Tomohon. This study uses a quantitative design with a cross sectional approach. The population in this study is all employees of PT PLN (Persero) ULP Tomohon as many as 62 people with a total sampling technique. Data were collected using a Likert scale questionnaire and analyzed using the Spearman Rank correlation test. The results of the study showed that most of the respondents had the implementation of SMK3 and employee performance in the high category. The results of the correlation test showed that there was a significant and strong relationship between the implementation of SMK3 and employee performance. This shows that the better the implementation of SMK3, the higher the performance of employees. There is a significant relationship between the implementation of SMK3 and employee performance at PT PLN (Persero) ULP Tomohon.